EVALUASI KINERJA DIRECT EXPANSION SOLAR-ASSISTED HEAT PUMP WATER HEATER KAPASITAS 30 LITER DENGAN MENGGUNAKAN REFRIGERAN R134A - Irawan, Teguh; Mainil, Rahmat Iman; Aziz, Azridjal (Jurnal Rekayasa Mesin, 2024)
Experiments were carried out to determine the performance of a direct expansion solar assisted heat pump water heater (DX-SAHPWH) which mainly consists of an evaporator panel with a surface area of ​​0.23 m2, a rotary compressor with an input power of 122.5 W, an insulated water tank that has been wrapped around a condenser with a diameter of 0.024 m and a length of 15 m and a capillary tube with a diameter of 0.001 m and a length of 1.61 m. Tests were carried out in open spaces, enclosed spaces and air-conditioned rooms exposed to direct sunlight. The results of this test are that the highest coefficient of performance (COP) on the DX-SAHPWH system is obtained at 1,25 and the smallest COP is obtained at 0.60. The higher intensity of solar radiation has a positive effect on the performance of the DX-SAHPWH system, which results in the heat transfer rate at water (Q wm) increases, the time required for heating is faster, and the COP of the DX-SAHPWH system increases.